Bronchial Asthma A Guide for Practical Understanding and Treatment - Gershwin, M. Eric; Albertson, Timothy E. (Current Clinical Practice, 2006)
Hailed by professional journals and esteemed by primary care doctors everywhere, Bronchial Asthma: A Guide for Practical Understanding and Treatment has been fully updated to help physicians face the challenge of diagnosis and the management of asthma in every variety of patient subpopulation. Although this fifth edition continues to emphasize the definition, medications, and use of asthma treatment plans, it also focuses on the special needs patient, including the pediatric patient, the pregnant patient, and the patient undergoing surgery, as well as on the perennial issues of exercise and asthma, pulmonary aspergillosis, occupation, recreational drug use, and psychological/social considerations. Highlights for the fifth edition include a liberal use of tables and charts to make the book more practical and user-friendly, updates on the many new pharmaceuticals used to treat asthma, and first-time sections on food sensitivity and the diagnosis of asthma. Authoritative and easy to use, Bronchial Asthma: A Guide for Practical Understanding and Treatment, Fifth Edition, continues the high standard established by the earlier editions, providing a basic framework for successful individualized treatment of all patients suffering from this debilitating disease.